Language, Power, and Ideology: A Critical Discourse Analysis of Nelson Mandela’s Speeches - Rida Khan; Dr. Hafiz Javed ur Rehman (Journal for Social Science Archives, 2025)
This study critically examines Nelson Mandela’s political rhetoric through Fairclough’s Critical Discourse Analysis (CDA) framework, focusing on how language constructs and conveys ideology. By analyzing three of Mandela’s landmark speeches—his 1994 Presidential Inaugural Address, the 2000 Laureus World Sports Awards speech, and the 2004 Johannesburg press conference—the research explores the intersection of language, power, and ideology in post-apartheid South Africa. Using Fairclough’s three-dimensional CDA model (text, discursive practice, and sociocultural practice), the study identifies key ideological components such as freedom, unity, reconciliation, and equality, which underpin Mandela’s vision of a democratic and inclusive nation. Through rhetorical strategies including metaphor, repetition, inclusivity, and moral appeals, Mandela’s discourse not only reflected his ideological commitments but also reshaped collective consciousness toward national healing. The analysis reveals how his linguistic choices embodied resistance, reconciliation, and transformation, linking individual narratives with broader sociopolitical realities. The study contributes to CDA scholarship by illustrating how political language operates as a tool of both ideological reproduction and social transformation, offering insights into the power of discourse in leadership and nation-building.